Challenges and a Strategy for Agricultural BMP Monitoring and Remediation of Nitrate Contamination in Unconsolidated Aquifers. Issue 1 (27th February 2015) - Rudolph, D.L.; Devlin, J.F.; Bekeris, L.
Abstract: Nitrate in groundwater and surface water is among the most common contamination problems in the world. Efforts to reduce the loss of excess nutrients at the regional scale currently focus on Best Management Practices (BMPs) designed to facilitate the optimal use of fertilizers, adjusted for specific site conditions. Performance monitoring of regional BMPs has proven to be problematic owing to the large areal scales, the inherent heterogeneity of nutrient mobility on landscapes and in the subsurface, and the extended time lag between implementation and overall improvements in groundwater quality. In order to shorten the time for useful assessments of progress and for the beneficial results to be realized, a strategy is proposed here with specific application to unconsolidated granular aquifers. First, a novel approach for quantifying BMP performance in the short term is demonstrated involving the monitoring of transient nitrate storage in the unsaturated zone. Secondly, a temporary remediation method based on in situ denitrification is implemented for reducing nitrate levels in public supply wells in the interim period until the full influence of the regional nutrient management BMPs is realized. The remediation approach incorporates a passive component that necessitates enhanced site characterization methods including high definition assessments of aquifer properties and groundwater velocity. The preliminary findings from a series of field investigations conducted between 2004 and 2011 at a site in southern Ontario indicate that this combined two‐step strategy may be capable of providing short‐term quantifiable evidence of BMP performance and also of attenuating nitrate to desirable levels during the time lag period between implementation of the BMPs and the arrival of their desired beneficial effects on the quality of public well water supplies. This may avoid the need to construct permanent above‐ground water treatment facilities that could eventually become redundant.